Provides a New Way to Enhance Security in the Linux Operating System - Hamid Reza Ganji; Kiarash Aghakhani (Ital Publication, 2018)
The security of the configuration of files in the Linux operating system depends on many factors that can be referenced to the system level and the applicable level. The most important thing about the security of Linux operating systems is its dynamism, for example, when you secure your Linux system, it will not stay safe forever, because applications and cyber criminals through new threats and/or new exploits that are packaged Systems or applications that cause the operating system to become unsafe, for this reason, we need a secure operating system. The main purpose of this article is to provide a new way to enhance the security of the Linux operating system. For this purpose, how can simple, continuous, and practical Linux environment be secured, solutions are presented, also based on performance analysis of the proposed method and evaluation parameters for existing systems against the proposed system, the superiority of this method is introduced.